WISATA HALAL DI BEBERAPA NEGARA ASEAN - Yuli Arisanti; Afan Kurniawan (Jurnal Inovasi Penelitian, 2022)
Muslim travelers are potential market and are currently growing rapidly. People in tourism industry is aware about this phenomenon. This study was conducted to find out how the current development of halal tourism or muslim friendly tourism in the Southeast Asian region of ASEAN members. The research was conducted with descriptive qualitative methods, data collection was carried out by studying literature through scientific journal articles, books and websites. The countries studied were Indonesia, Malaysia and Singapore. Malaysia is a country that is fast in seizing halal tourism opportunities and a pioneer in meeting the needs of Muslim travelers. Indonesia as a country with the world's largest Muslim population is starting to catch up with Malaysia, which has often won various halal tourism awards. Singapore as a non-OIC (Organization of Islamic Cooperation) country is able to become a leader in halal tourism among non-OIC countries. In order to become the world's best halal tourist destination, Indonesia needs to encourage the awareness of tourism industry players to carry out halal certification on products and services.